Energy management in the water sector – Comparative case study of Germany and the United States - Thomas Voltz; Thomas Grischek (Water-Energy Nexus, 2018)
The US and Germany are compared on their energy use and water use, the factors that influence them and the resulting efficiency. Water abundance and an energy-focused political atmosphere makes energy a top priority for the water sector in Germany. Water stress, leaky pipe infrastructure and comparatively fledgling energy policy make energy a low priority among US water/wastewater utilities (WWUs). Although developed by a US-led team in 2011, the ISO 50001 energy management standard has as of 2016 been adopted and certified by more than 9000 German companies, including 200 WWUs, compared to 47 companies in the US, including one single WWU. While adoption of ISO 50001 may continue growing at a rate similar to past management standards ISO 9001 and 14001, experience in Germany and elsewhere shows that it might be more effectively used in the US as a policy mechanism in conjunction with financial incentives. A water savings of 81% would be required to reach German levels by reducing water losses (23% thereof) and water use (77%). The consequent embedded energy savings (virtually contained in the water savings) is 39% of the maximum possible energy savings in the water sector. The remaining 61% comes from long-term technical improvements, assuming a savings quota of 30%. For the entire water sector in the US, this means a maximum energy savings of nearly 50% (34.2 TWh). Achieving even a fraction of this optimistic estimate would lead to substantial savings. Keywords: Energy management, Energy efficiency, WWUs, ISO 50001, US-Germany comparison, Energy-water nexus